THE EFFECT OF SOCIAL MEDIA MARKETING AND CUSTOMER RELATIONSHIP MANAGEMENT ON CUSTOMER RETENTION IN TOKOPEDIA - Inri Hana Menajang; Paulus Kindangen; Shinta J.C. Wangke (Universitas Sam Ratulangi, 2023)
The purpose of this research is to find out the effect of social media marketing and customer relationship management on customer retention in Tokopedia. This study uses the quantitative method and using multiple linear regression test to determine the effect of social media marketing and customer relationship management on customer retention. The sample size used for this research was 100 users of Tokopedia that lived in Manado. The sampling technique used is a purposive sampling method and the data collection method is in the form of a questionnaire that is run through Google Form. Testing and data analysis in this study using SPSS software. The results shows that Social Media Marketing (X1) partially have a positive and significant influence on Customer Retention (Y). Customer Relationship Management (X2) partially have a positive and significant influence on Customer Retention (Y). Social Media Marketing (X1) and Customer Relationship Management (X2) simultaneously have a positive and significant influence on Customer Retention (Y). Adjusted R Square value obtained from the results of the coefficient of determination (R2) of 0.451 explains that 45.1% of customer retention can be explained by social media marketing and customer relationship management. While the remaining 54.9% is explained by other variables not examined in this study. Keywords: social media marketing, customer relationship management, customer retention